Optimizing AI user experience: Analyzing the impact of trust, engagement, and emotional satisfaction using multiple linear regression - Binh, Pham Thanh; Thanh, Nguyen Nghi (Edelweiss Applied Science and Technology, 2026)
This study examines the effects of trust in AI, happiness from AI interactions, user engagement, AI-influenced purchase intention, and reliance on AI on overall AI user experience. Using a multiple linear regression model and survey data from 200 AI users in Vietnam, the results show that all five factors significantly influence AI user experience (p < 0.001). Among them, happiness from AI interactions emerges as the strongest predictor (β = 0.336), highlighting the critical role of positive emotional responses. Engagement (β = 0.266) and reliance on AI (β = 0.253) also show substantial effects, indicating that frequent interaction and reliance on AI enhance the user experience. Trust in AI (β = 0.230) contributes significantly, emphasizing the importance of transparency and reliability in AI systems. In contrast, AI-driven purchase intention (β = 0.189) shows a weaker influence. The findings underscore the importance of human-centered and ethical AI design. Future research should explore cross-cultural variations and the ethical implications of AI reliance.